Poems From The Faux Normal - Jaicten, Ges (Likhaan: The Journal of Contemporary Philippine Literature; Vol 16 No 2 (2022): Dx Machina: Philippine Literature in the Time of COVID-19, 2024)
In an effort to make sense of the flurry of news and pandemic-caused events, this writer spent many nights laboring on poems which reflect his experiences during these trying times. As part of a collective project, these poems serve to represent the Filipino experience of the pandemic through the microscopic view of the writer who lived by himself during this period.